Assertiveness : practical approach - Holland, Stephanie; Ward, Clare (Bicester : Winslow, 1990)
This book is about: Introduction to assertiveness; Behaviour types; Being assertive; Our right to be assertive; ...
Keywords: Communication; Assertiveness; Interpersonal relations; Communication; Interpersonal communications; Assertiveness training; Assertiveness (Psychology) -- Problems, exercises, etc; Assertiveness